Tracking life and death of carbon nitride supports in platinum-catalyzed vinyl chloride synthesis - Vera Giulimondi; Mikhail Agrachev; Sergei Kuzin; José Manuel González-Acosta; Andrea Ruiz-Ferrando; Frank Krumeich; Federica Bondino; Yung-Tai Chiang; Matteo Vanni; Gunnar Jeschke; Núria López; Javier Pérez-Ramírez (Nature Communications)
Abstract Deactivation of metal-based catalysts for vinyl chloride synthesis via acetylene hydrochlorination is often dictated by indispensable, catalytically-active carbon supports, but underlying mechanisms remain unclear. Carbon nitrides offer an attractive platform for studying them thanks to ordered structure and high N-content, which facilitates coking. Herein, we monitor the life and death of carbon nitride supports for Pt single atoms in acetylene hydrochlorination, demonstrating that specific N-functionalities and their restructuring cause distinct deactivation mechanisms. Varying polymerization and exfoliation degrees in pristine carbon nitrides (i.e., −NH x termination and N-vacancy concentrations), we establish graphitic and pyridinic N-atoms as C2H2 adsorption sites and pyridinic N-vacancies as coking sites through kinetic and spectroscopic analyses. Uniquely suited for probing point defects, operando electron paramagnetic spectroscopy, coupled to simulations, reveals that HCl drives depolymerization, by protonating heptazine-linking graphitic N-atoms, and generates graphitic N-vacancies, forming NH3. These reduce C2H2 adsorption and promote radical polymerization into coke, respectively, without altering Pt atoms. Design guidelines to mitigate deactivation are discussed, highlighting the importance of tracking active functionalities in carbons.